2018
DOI: 10.1016/j.wem.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Death on the Dome: Epidemiology of Recreational Deaths on Half Dome in Yosemite National Park

Abstract: We identified 31 Half Dome deaths over 85 y. A minority were attributable to unfavorable weather or unskilled hiking participants. Climber registration could provide dependable denominators for accident incidence statistics. A renewed focus on suicide prevention is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Compared to a nationwide mortality of 6.2 deaths per year in Austria, the data from Yosemite show a total number of deaths of n = 12 in a 10-year timeframe for a single summit [2]. The differentiation of causes leading to death in the history of the summit revealed that 10 of 31 traceable deaths were related to hiking (n = 5) and cable handrails (n = 5) [1].…”
Section: Emergencies Leading To Deathmentioning
confidence: 90%
See 1 more Smart Citation
“…Compared to a nationwide mortality of 6.2 deaths per year in Austria, the data from Yosemite show a total number of deaths of n = 12 in a 10-year timeframe for a single summit [2]. The differentiation of causes leading to death in the history of the summit revealed that 10 of 31 traceable deaths were related to hiking (n = 5) and cable handrails (n = 5) [1].…”
Section: Emergencies Leading To Deathmentioning
confidence: 90%
“…Until now, peer-reviewed literature reporting on via ferrata accidents, injury patterns and mechanisms, as well as outcome, has been scarce. To our knowledge, only two studies from Yosemite National Park, CA, have been published to date [1,2]. Both concentrated on Half Dome, a summit reached by a 23 km to 26 km roundtrip hike followed by the final 146 m, which is equipped with cable handrails.…”
Section: Introductionmentioning
confidence: 99%
“…5 Thirty-two fatalities have occurred on Half Dome over the last 85 y, including a fall from the cables in May 2018; however, less than 20% of these have been related to activity on the cable handrails. 5 Hikers asked to analyze photographs of the cable route perceived an increased risk when the number of people at one time (PAOT) on the cable handrails exceeded 70 persons. 6 Consulting reports have demonstrated significant decreases in PAOT on the cable handrails, subdome, and Half Dome summit after permitting.…”
Section: Introductionmentioning
confidence: 99%
“…On Mt Cook (3724 m, NZ), 1.87 deaths per 1000 exposure days were reported [64]. Eleven deaths were found during traditional climbing on Half Dome (2694 m, US) over a period of 85 years [65]. Thirteen fatalities were recorded in 3.5 years in the Yosemite National Park (<4000 m, US) and 6% of the rock climbing injuries registered at the local medical clinic or rescue team were fatal [63].…”
Section: Resultsmentioning
confidence: 99%